A Comprehensive Literature Review on the Impact of Cyberattacks on Accounting Practices and Security Measures - Jessy Juanda (Fairness, 2025)
Objective: This research aims to investigate the increasing cybersecurity threats to accounting information systems and assess the effectiveness of cybersecurity governance in mitigating these risks. This research emphasizes the importance of integrating cybersecurity measures into accounting practices to enhance resilience against cyberattacks. Research Design & Methods: This study uses the Systematic Mapping Study method to comprehensively analyze the existing literature, identify research gaps, and provide a structured overview of cybersecurity governance in accounting. A total of 45 articles from the Scopus database were selected using Publish or Perish 8, covering publications from 2014 to 2024. Findings: The study revealed that Cyberattacks on accounting systems pose a threat to financial, operational, and public trust. Effective mitigation requires the integration of AI, blockchain, encryption, and employee training, along with investments in regulatory compliance and security to maintain system integrity. Implications & Recommendations: Practically, organizations should enhance cybersecurity awareness, adopt stricter security policies, and integrate predictive analytics to effectively mitigate cyber threats. Boards of directors play a crucial role in overseeing cybersecurity governance and ensuring the implementation of sustainable risk management strategies. The theoretical implications highlight the need for further empirical research to assess cybersecurity measures across diverse industries and regulatory frameworks.Contribution & Value Added: This study contributes to the growing literature on cybersecurity in accounting, offering insights into emerging threats and effective mitigation strategies. The study also underscores the importance of a holistic, technology-based approach to cybersecurity management, ensuring long-term resilience in accounting information systems.